Fresco Painting of Post-Byzantine Macedonia. General Remarks and Prospects for Study - Onufrienko, Maksim O. (Actual Problems of Theory and History of Art, 2024)
The article is dedicated to the study of post-Byzantine painting in Macedonia from the late 15th to the early 18th century. The post-Byzantine period in Macedonian art is considered to begin in the late 15th century, as the influence of northern Greek masters became dominant during this time. Artists from the northern Greek villages of Linotopi and Grammousta developed their style based on late Byzantine painting: the deep spatial composition and sculptural qualities were replaced by a more decorative approach, emphasizing ornaments and local colors. These artists emerged as the leading artistic force in Macedonia, their stylistic preferences shaping the tastes of patrons and forming the local artistic tradition. The painting style of Slavic artistic workshops essentially merged with northern Greek painting, to the extent that works by Slavic masters are indistinguishable from those of artists from Kastoria and Linotopi. A general artistic crisis in the first half of the 17th century, characterized by uniformity and reproduction of established stylistic formulas, spurred artists to seek new solutions. One way of introducing innovations was the use of Western European engravings, which enriched the local artistic language and prepared it for closer interaction with Western culture in the future. The discussion of post-Byzantine art in the region can be concluded in the first half of the 18th century when new Baroque artistic trends began to emerge in the Balkans, and Mount Athos became the center of Orthodox art. This period also coincided with the decline of the Ohrid Archbishopric’s influence, as it lost its status of a major ecclesiastical center.This work is supported by the Russian Science Foundation (grant 20-18-00294-P) and done at the Research Institute of Theory and History of Architecture and Town Planning —  branch of the Central Research and Project Institute of the Construction Ministry of Russia.
Keywords: Macedonia; post-Byzantine art; monumental painting; the Balkans; Kastorian masters